Charge generation by ultra-stretchable elastomeric electrets. Issue 7 (6th February 2017) - Ko, Yee Song; Nüesch, Frank A.; Opris, Dorina M.
Abstract : Novel piezoelectric elastomers are synthesized and their long term stability and piezoelectric properties are investigated. Abstract : Novel piezoelectric elastomers are synthesized and their long term stability and piezoelectric properties are investigated. They are thin film composites of specially designed polymer nanoparticles with high glass transition temperatures ( T g ) and side groups with large permanent dipoles, which are embedded in chemically crosslinked polydimethylsiloxane matrices. To obtain a piezoelectric material, the initially randomly oriented polar groups in the nanoparticles are poled in a strong electric field while the film is heated above the T g of the nanoparticles. Under these conditions the polar groups orient in the direction of the electric field and the achieved orientation is subsequently frozen-in by cooling the material back to room temperature. A permanent polarization responsible for the piezoelectricity is induced in the elastomers. All composites are elastic and can be strained up to 600%. The lateral piezoelectric coefficient d 31 of the composites are found to first decrease over a period of several days before ultimately stabilizing. The largest d 31 value obtained, 12.1 pC N −1, is comparable to commercially available materials which are not elastic. Two composites exhibit promising thermal stability at 50 °C and generate a maxim of 2.5 V when strained. The novel elastic electret materials described in this paper are likely to find application as stretchable sensors, soft electronics, transducers and energy harvesters. Another important aspect of this work is the abundantly available combinations of elastic matrices and high T g polar polymers, which will allow the creation of elastic electrets with tailor-made properties in the future.